2019
DOI: 10.3390/ma12071104
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Chemistry and Structural Stability of AlNb3 Enabled by Antisite Defects Formation

Abstract: First-principles evolutionary algorithms are employed to shed light on the phase stability of Al–Nb intermetallics. While the tetragonal Al3Nb and AlNb2 structures are correctly identified as stable, the experimentally reported Laves phase of AlNb3 yields soft phonon modes implying its dynamical instability at 0 K. The soft phonon modes do not disappear even upon elevating the temperature in the simulation up to 1500 K. X-Ray diffraction patterns recorded for our powder-metallurgically produced arc cathodes, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 42 publications
2
5
0
Order By: Relevance
“…The spectra are shown in figure 6 and can be used to investigate their influence on the dynamic stability of the system. Firstly, figure 6(a) correctly identified the phonon spectrum of the parent Nb 3 Al (without defects), which is consistent with previous studies [20]. From the density of phonon states of Nb 3 Al, it can be seen that the main element affecting the dynamic stability of the system is Nb, while the vibration frequency of Al element is mainly in the high energy region.…”
Section: Antisite Defect's Effect On Dynamic Stability Of Nb 3 Alsupporting
confidence: 88%
See 1 more Smart Citation
“…The spectra are shown in figure 6 and can be used to investigate their influence on the dynamic stability of the system. Firstly, figure 6(a) correctly identified the phonon spectrum of the parent Nb 3 Al (without defects), which is consistent with previous studies [20]. From the density of phonon states of Nb 3 Al, it can be seen that the main element affecting the dynamic stability of the system is Nb, while the vibration frequency of Al element is mainly in the high energy region.…”
Section: Antisite Defect's Effect On Dynamic Stability Of Nb 3 Alsupporting
confidence: 88%
“…He et al [19] proposed another dynamic description system and pointed out that the proportion of Nb in the stable phase of Nb 3 Al ranges from 0.79 to 0.84. Koutná et al subsequently confirmed such a peculiar compositional window of Nb 3 Al [20]. When the thermal movement of atoms in intermetallic compounds or their deviation from the stoichiometric ratio happens, there can inevitably exist point defects in the crystal, such as vacancy, antisite defects, etc.…”
Section: Introductionmentioning
confidence: 95%
“…Despite the fact that many recent activities have been directed towards big-data and machine learning [2,3,4], there are still many topics which require individualised treatments. An example of such a problem is the discrepancy between the experimentally and theoretically reported stability and chemistry of the Nb 3 Al phase also published in this special issue [5]. Starting from the pioneering works of Grabowski and co-workers [6,7,8,9,10,11], the first-principles thermodynamics by including the vibrational contribution to the free energy within the harmonic approximation have became fairly routine.…”
Section: Introductionmentioning
confidence: 99%
“…We note that according to 0 K DFT calculations, the only stable structures within the binary Nb-Al system are bcc-Nb, Nb 2 Al, NbAl 3 , and fcc-Al (all marked by red triangles). Nb 3 Al, although present in the experiments, is dynamically unstable (even at higher temperatures) and was proposed to be stabilized by antisite defects [33]. 9 for the composite and in figure 10 for the intermetallic cathode types.…”
Section: Arc Voltages and Cohesive Energiesmentioning
confidence: 87%
“…The Nb-Al intermetallics, NbAl 3 , Nb 2 Al, and Nb 3 Al, were assumed to adopt the tetragonal DO 22 (I4/mmm, #139), tetragonal D8 b (P4 2 /mnm, #136), and cubic A15-type (Pm3n, #223) phase, respectively. Additionally, low-energy metastable Nb x Al -x 1 structures were predicted [33] employing first-principles evolutionary algorithms as implemented in the USPEX (universal Structure Predictor: Evolutionary Xtallography) code [34][35][36] featuring local optimization, real-space representation and flexible physically motivated variation operators. The cohesive energies (E coh ) were evaluated according to…”
Section: Approximation Of Cohesive Energiesmentioning
confidence: 99%